Mediators of physical exercise for improvement in cancer survivors' quality of life. Issue 3 (14th October 2013) - Buffart, L. M.; Ros, W. J. G.; Chinapaw, M. J. M.; Brug, J.; Knol, D. L.; Korstjens, I.; van, E.; Mesters, I.; van den, B.; Hoekstra‐Weebers, J. E. H. M.; May, A. M.
Abstract Objective Mediating mechanisms of a 12‐week group‐based exercise intervention on cancer survivors' quality of life (QoL) were examined to inform future exercise intervention development. Methods Two hundred nine cancer survivors ≥3 months posttreatment (57% breast cancer) aged 49.5 (±10.4) years were assigned to physical exercise (n = 147) or wait‐list control (n = 62). QoL, fatigue, emotional distress, physical activity, general self‐efficacy and mastery were assessed at baseline and post‐intervention using questionnaires. Path analysis was conducted using Mplus to explore whether improved physical activity, general self‐efficacy and mastery mediated the effects of exercise on fatigue and distress and consequently QoL. Results The intervention was associated with increased physical activity (β = 0.46, 95% confidence interval (CI) = 0.14;0.59), general self‐efficacy (β = 2.41, 95%CI = 0.35;4.73), and mastery (β = 1.75, 95%CI = 0.36;2.78). Further, the intervention had both a direct effect on fatigue (β = −1.09, 95%CI = −2.12;0.01), and an indirect effect (β = −0.54, 95%CI = −1.00;−0.21) via physical activity (β = −0.29, 95%CI = −0.64;−0.07) and general self‐efficacy (β = −0.25, 95%CI = −0.61;−0.05). The intervention had a borderline significant direct effect on reduced distress (β =−1.32, 95%CI =−2.68;0.11), and a significant indirect effect via increased general self‐efficacy and mastery (β =−1.06, 95%CI =−1.89;−0.38). Reductions in fatigue (β =−1.33, 95%CI =−1.85;−0.83) and distress (β =−0.86, 95%CI =−1.25;−0.52) were associated with improved QoL. Further, increased physical activity was directly associated with improved QoL (β = 3.37, 95%CI = 1.01;5.54). Conclusion The beneficial effect of group‐based physical exercise on QoL was mediated by increased physical activity, general self‐efficacy and mastery, and subsequent reductions in fatigue and distress. In addition to physical activity, future interventions should target self‐efficacy and mastery. This may lead to reduced distress and fatigue, and consequently improved QoL of cancer survivors. Copyright © 2013 John Wiley & Sons, Ltd.